2022
DOI: 10.3390/ijerph19169810
|View full text |Cite
|
Sign up to set email alerts
|

Family Needs Checklist: Development of a Mobile Application for Parents with Children to Assess the Risk for Child Maltreatment

Abstract: Child maltreatment (CM) has been enormously studied. However, a preventive practice still requires comprehensive and effective instruments to assess the risks for CM in a family context. The aim of this study is to describe the development process of an evidence-based CM risk assessment instrument (Family Needs Checklist, FNC) for primary prevention online utilization. This article reports the development process of the checklist and its mobile application, consisting of a systematic literature review, identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 84 publications
(168 reference statements)
1
5
0
Order By: Relevance
“…Several women described that their children had indeed witnessed violence and suffered negative consequences as a result of IPV. Similar to those children, several participants reported childhood trauma of their own (see Table 1 ), which also aligns with past findings on the intergenerational transmission of violence and abuse [ 16 , 17 , 18 ]. In general, our participants described how their childhoods and experiences as young adults had impacted their lives as adults, as Norman et al have additionally identified [ 19 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several women described that their children had indeed witnessed violence and suffered negative consequences as a result of IPV. Similar to those children, several participants reported childhood trauma of their own (see Table 1 ), which also aligns with past findings on the intergenerational transmission of violence and abuse [ 16 , 17 , 18 ]. In general, our participants described how their childhoods and experiences as young adults had impacted their lives as adults, as Norman et al have additionally identified [ 19 ].…”
Section: Discussionsupporting
confidence: 88%
“…IPV is one of the risks of intergenerational transmission of violence and/or maltreatment [ 16 , 17 , 18 ]. All forms of violence can be expected to severely impact children and their lives as adults [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, they reported families' support needs related to other issues, such as coping and intimate partnership. Problems in these issues are risk factors of FV, especially CM (Rantanen, Nieminen, et al, 2022). Public health nurses in our study noticed more of these support needs in families with FV compared to other families.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FNC can be used for primary prevention among the general population. Above all, there is a need to discuss any worries parents have systematically and in dialogue with families, and also ask clients and families about violence, whenever needed (Rantanen, Nieminen, et al, 2022).…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation